Injuries in elite male kitesurfers - Eliseo Andreu-Cabrera; Marcelo Jove-Tossi; Concepción Suárez-Llorca; Juan M. Cortell-Tormo; José A. Pérez-Turpin; Vicente Carrasco-Embuena (FEADEF, 2011)
A relatively new extreme sport, kitesurf hasn't received the kind of scientific scrutiny found with other more traditional sports. Currently, the pattern and rate of kiteboarding injuries are largely unclear. The objective was to identify common injury patterns as well as potential areas in which prevention measures might be instituted. A descriptive epidemiological study was designed and a retrospective questionnaire was performed on 38 elite kitesurfers taking part in the World Cup Fuerteventura 2008. The ankle is the part of the body most affected by injury p<0.01, whilst the Course Race category accounted for 68.4% of injuries, compared with 31.6% in the Freestyle category. Said injuries occurred more frequently when training (76.3%; p<0.01) than during competitions and acute injuries were the most common. These results show the need to establish new prevention methodologies, above all for the legs and specifically for the ankle area and in the Course Race category, as well as the use of foot protections